Selection of Maceration Solvent for Natural Pigment Extraction from Red Fruit (Pandanus conoideus Lam) - Purnomo, Tantyo Ardy Bintoro; Kurniawan, Yehezkiel Steven; Kesuma, Ruth Febriana; Yuliati, Leny (Ma Chung Research Center for Photosynthetic Pigments, 2020)
Red fruit (Pandanus conoideus Lam) is rich with red-orange natural pigments, such as Î²-carotene. In this work, the solvent selection was investigated to extract the Î²-carotene from the red fruit via a simple maceration technique. Three types of solvents were used in the maceration, which were distilled water, ethanol, and acetone. The obtained extracts were characterized using spectrophotometer ultraviolet-visible (UV-visible), Fourier transform infrared (FTIR) and spectrofluorometer. The different solvents gave different spectroscopic information, suggesting that the solvent selection influenced the type of the extracted compounds. Among the examined solvents, acetone was found to be the most effective one to extract the Î²-carotene. The presence of the Î²-carotene pigment in acetone extract was confirmed by the appearance of the absorption peak at 476 nm on its UV-visible spectrum, while from its FTIR spectrum, the C-H sp3 functional group of Î²-carotene was found at 2924 and 2854 cm-1. In addition, the emission peak of Î²-carotene was found at 394 and 561 nm. This study confirmed that acetone performed as a better maceration solvent for Î²-carotene as compared to the distilled water and ethanol, which would be strongly related to the non-polar property of the acetone.